2014
DOI: 10.4049/jimmunol.1401699
|View full text |Cite
|
Sign up to set email alerts
|

Intraclonal Diversity in Follicular Lymphoma Analyzed by Quantitative Ultradeep Sequencing of Noncoding Regions

Abstract: Cancers are characterized by genomic instability and the resulting intra-clonal diversity is a prerequisite for tumor evolution. Therefore, metrics of tumor heterogeneity may prove to be clinically meaningful. Intra-clonal heterogeneity in follicular lymphoma (FL) is apparent from studies of somatic hypermutation (SHM) caused by Activation Induced Deaminase (AID) in IGH. Aberrant SHM (aSHM), defined as AID activity outside of the IG loci, predominantly targets non-coding regions causing numerous “passenger” mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…We found that BCL2 , followed by BCL6 , showed the most consistent and differential aSHM signal in FL specimens, with SNVs in 12/12 FL cases and 0/3 in the reactive LN controls. The range of SNVs in BCL2 varied widely, from 2 to 101 per patient; raising the possibility that overall BCL2 aSHM rate might be clinically informative through risk stratification [ 54 ]. BCL6 shows a similar pattern, but with a much lower overall aSHM rate, in the range of 2 to 39 SNV per patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that BCL2 , followed by BCL6 , showed the most consistent and differential aSHM signal in FL specimens, with SNVs in 12/12 FL cases and 0/3 in the reactive LN controls. The range of SNVs in BCL2 varied widely, from 2 to 101 per patient; raising the possibility that overall BCL2 aSHM rate might be clinically informative through risk stratification [ 54 ]. BCL6 shows a similar pattern, but with a much lower overall aSHM rate, in the range of 2 to 39 SNV per patient.…”
Section: Discussionmentioning
confidence: 99%
“…The frequencies associated with MFC varied from 10% to 45% (median of 20%) and in all but one case (FL-134) the majority of SNVs in any given tumor had frequencies consistent with their current MFC. Several FL specimens (5/12) had no SNVs outside the MFC; three with a low overall mutation rate (<0.7%) and two with a different type of FL (Grade 3 vs. Grades 1 and 2), suggestive of a possible biological aspect to this finding [ 54 ]. Of the remaining FL specimens, the vast majority (over 80%) of the SNVs outside the MFC were found at ≤3%, while over half were ≤1% (see Additional file 4 : Table AF1).…”
Section: Discussionmentioning
confidence: 99%
“…Next‐generation sequencing (NGS) of immunoglobulin heavy locus (IGH) gene rearrangements for the monitoring of minimal residual disease in patients with leukaemia or myeloma has already been proved useful . In molecular pathology, where formalin‐fixed paraffin‐embedded (FFPE) tissues are frequently used, resulting in suboptimal DNA quality, IG‐rearrangement assessment has different requirements and has only just begun . In the current study, we have investigated semi‐conductor sequencing using the Ion Torrent Personal Genome Machine (Ion PGM) for IG rearrangement assessment in pathology.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13] In molecular pathology, where formalinfixed paraffin-embedded (FFPE) tissues are frequently used, resulting in suboptimal DNA quality, IG-rearrangement assessment has different requirements and has only just begun. 14,15 In the current study, we have investigated semi-conductor sequencing using the Ion Torrent Personal Genome Machine (Ion PGM) for IG rearrangement assessment in pathology. Because of its short running time, 16,17 the Ion PGM is often used in molecular pathology laboratories for mutation detection in oncogenes in the context of prediction of therapy response in which a short turnaround time is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, AID was found to be important for the IGH/ CMYC rearrangements present in some B lineage neoplasms (murine plasmacytomas, human Burkitt lymphoma, and other lymphomas) (37). More recent studies have identified numerous genes harboring oncogenic mutations that can be traced backed to AID because of their unique mutational signatures (3842). Overall, these findings have clarified the natural history of a substantial subset of lymphomas.…”
mentioning
confidence: 99%